A multiscale assessment of Red-tailed Hawk reproductive success relative to urban density and habitat type. Issue 1 (12th November 2020) - White, Justin H; Brown, Jessi L; Ormsby, Zachary E
Abstract: Despite the unique threats to wildlife in urban areas, many raptors have established successfully reproducing urban populations. To identify variations in raptor breeding ecology within an urban area, we compared metrics of Red-tailed Hawk reproductive attempts to landscape characteristics in Reno and Sparks, NV, USA during the 2015 and 2016 breeding seasons. We used the Apparent Nesting Success and logistic exposure methods to measure nesting success of the Red-tailed Hawks. We used generalized linear models to relate nesting success and fledge rate to habitat type, productivity to hatch date (Julian day) and hatch date to urban density. Nesting success was 86% and 83% for the respective years. Nesting success increased in grassland-agricultural and shrub habitats and decreased in riparian habitat within the urban landscape. Productivity was 2.23 and 2.03 per nest for the breeding seasons. Fledge rates were 72% and 77%, respectively, and decreased in riparian areas. Nestlings hatched earlier with increased urban density and earliest in suburban areas, following a negative quadratic curve. Nesting success and productivity for this population were high relative to others in North America. Productivity increased in habitats where ground prey was more accessible. We suggest that suburban areas, if not frequently disturbed, provide sufficient resources to sustain Red-tailed Hawks over extended periods. As urban expansion continues in arid environments globally, we stress that researchers monitor reproductive output across the urban predator guild to elucidate patterns in population dynamics and adaptation.